2019
DOI: 10.1093/rheumatology/kez589
|View full text |Cite
|
Sign up to set email alerts
|

All-cause and cause-specific mortality in ANCA-associated vasculitis: overall and according to ANCA type

Abstract: Objective The objective of this study was to evaluate causes of death in a contemporary inception cohort of ANCA-associated vasculitis patients, stratifying the analysis according to ANCA type. Methods We identified a consecutive inception cohort of patients newly diagnosed with ANCA-associated vasculitis from 2002 to 2017 in the Partners HealthCare System and determined vital status through the National Death Index. We deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 29 publications
3
61
0
1
Order By: Relevance
“…Similarly, an increased risk of cardiovascular events (coronary artery disease and ischemic stroke) is also observed in patients with AAV [ 132 ]. Similar to VTE, most cardiovascular events occur in the first year after diagnosis [ 132 ]; both disease activity and ANCA type appear to be associated with cardiovascular risk [ 133 , 134 ]. Thus, aggressive cardiovascular risk factor assessment and modification should be integrated within the therapeutic approach of AAV patients.…”
Section: Management Of Kidney Involvement In Aavmentioning
confidence: 99%
“…Similarly, an increased risk of cardiovascular events (coronary artery disease and ischemic stroke) is also observed in patients with AAV [ 132 ]. Similar to VTE, most cardiovascular events occur in the first year after diagnosis [ 132 ]; both disease activity and ANCA type appear to be associated with cardiovascular risk [ 133 , 134 ]. Thus, aggressive cardiovascular risk factor assessment and modification should be integrated within the therapeutic approach of AAV patients.…”
Section: Management Of Kidney Involvement In Aavmentioning
confidence: 99%
“…Despite tremendous improvements in prognosis, AAV is still associated with a significant increased risk of death, estimated about 2.7 times above that of the general population [73], with cardiac involvement being an important predictor of mortality [70,74]. Cardiovascular death is most common (7.1%), followed by death due to malignancy and infection [2]. MPO-ANCA-associated vasculitis patients carry a higher risk of CV death than PR3-ANCA-associated vasculitis patients [2], which may be a consequence of the more profound renal damage that typically occurs in MPA patients, or may be due to biochemical differences in these diseases, such as enhanced myeloperoxidase-mediated LDL oxidation, as has been identified in MPA patients [75].…”
Section: Events In Aavmentioning
confidence: 99%
“…Cardiovascular death is most common (7.1%), followed by death due to malignancy and infection [2]. MPO-ANCA-associated vasculitis patients carry a higher risk of CV death than PR3-ANCA-associated vasculitis patients [2], which may be a consequence of the more profound renal damage that typically occurs in MPA patients, or may be due to biochemical differences in these diseases, such as enhanced myeloperoxidase-mediated LDL oxidation, as has been identified in MPA patients [75].…”
Section: Events In Aavmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases with double seropositivity for both PR3- and MPO-ANCA are rarely seen, and are mainly associated with secondary forms of ANCA-associated vasculitis (i.e., in cocaine-induced forms or drug-induced vasculitis) [ 8 , 9 ]. Recent research found that the ANCA serotype better discriminates between genetic associations, therapeutic response, relapse risk, prognosis and co-morbidities (venous thromboembolic events and cardiovascular death) than a classification based on the clinical phenotype [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In addition, the respective ANCA serotype more closely relates to biomarkers of disease activity [ 17 ] and may help to identify novel therapeutic targets and predict response to current treatment regimens.…”
Section: Introductionmentioning
confidence: 99%